2015
DOI: 10.12680/balneo.2015.1086
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF CARDIOVASCULAR REHABILITATION IN PATIENTS ADMITTED TO THE “Dr Benedek Geza” Hospital of Rehabilitation IN CARDIOVASCULAR Diseases, COVASNA

Abstract: Background. Cardiovascular rehabilitation is an important objective of the treatment of cardiovascular patients in general, and ischemic heart disease patients in particular.The aim of the study is to monitor the effects of long-term cardiovascular rehabilitation in patients readmitted to the "Dr Benedek Geza" Hospital of Rehabilitation in Cardiovascular Diseases Covasna.Material and methods. The study included 92 patients with a mean age of 66.31±9 years, of which 63% women, who had two successive admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, the results of Suceveanu et al demonstrated significant differences for LdL-cholesterol and HdL-cholesterol changes for patients with main cardiovascular risk factors who attended a rehabilitation programme with hydrotherapy included [16]. mooventhan and nivethitha suggest that hydrotherapy is widely used to improve immunity and for the management of hypercholesterolemia and add that there is a lack of evidences on the impact of water of different salinity and temperature [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of Suceveanu et al demonstrated significant differences for LdL-cholesterol and HdL-cholesterol changes for patients with main cardiovascular risk factors who attended a rehabilitation programme with hydrotherapy included [16]. mooventhan and nivethitha suggest that hydrotherapy is widely used to improve immunity and for the management of hypercholesterolemia and add that there is a lack of evidences on the impact of water of different salinity and temperature [6].…”
Section: Discussionmentioning
confidence: 99%
“…Buziaş, Borşa, Slănic Moldova, Sangeorz Băi (2,3,6,7). Mofettes, as natural phenomena, are extremely rare in Europe and the rest of the world; except those present in Romania, they can be found only in Hungary, in Grotta di Cani near Naples, in Marienberg and Andernach in Germany, in Tiskory Lanz in Czechia, in Jawa island and in the Yellowstone Park in the USA (8).…”
mentioning
confidence: 99%
“…Mofette gas is indicated for certain diseases, such as peripheral arterial disease stage 1, 2 and 3, arteritis, venopathy, leg ulcers, chronic stable ischemic heart disease, stable hypertension stage 1 and 2, dermatological, gynecological diseases, chronic degenerative rheumatism (2,3). However, the major indication of mofette is in secondary prevention of cardiovascular disease and cardiovascular disease rehabilitation (6,7).…”
mentioning
confidence: 99%